Effect of pain neuroscience education after breast cancer surgery on pain, physical, and emotional functioning: a double-blinded randomized controlled trial (EduCan trial) - Dams, L.; Van Der Gucht, E.; Devoogdt, N.; Smeets, A.; Bernar, K.; Morlion, B.; Godderis, L.; Haenen, V.; De Vrieze, T.; Fieuws, S.; Moloney, Niamh; Van Wilgen, P.; et al. (2023)
Pain is one of the most common and long-lasting side effects reported by women surgically treated for breast cancer. Educational interventions may optimize the current physical therapy modalities for pain prevention or relief in this population. Pain neuroscience education (PNE) is an educational intervention that explains the pain experience not only from a biomedical perspective but also the psychological and social factors that contribute to it. Through a double-blinded randomized controlled trial (EduCan trial) it was investigated if PNE, in addition to the standard physiotherapy program immediately after breast cancer surgery, was more effective over the course of 18 months postoperatively than providing a biomedical explanation for pain. Primary outcome was the change in pain-related disability (Pain Disability Index, 0-70) over 12 months. Secondary outcomes included change in pain intensity, upper limb function, physical activity level, and emotional functioning over 4, 6, 8, 12, and 18 months postoperatively. Multivariate linear models for repeated (longitudinal) measures were used to compare changes. Preoperative and postoperative moderators of the change in pain-related disability were also explored. Of 184 participants randomized, the mean (SD) age in the PNE and biomedical education group was 55.4 (11.5) and 55.2 (11.4) years, respectively. The change in pain-related disability from baseline to 12 months postoperatively did not differ between the 2 groups (PNE 4.22 [95% confidence interval [CI]: 1.40-7.03], biomedical 5.53 [95% CI: 2.74-8.32], difference in change -1.31 [95% CI: -5.28 to 2.65], P = 0.516). Similar results were observed for all secondary outcomes. Future research should explore whether a more patient-tailored intervention would yield better results.